Integrasi Budaya Lokal dan Islam dalam Tradisi Mbabar Mbubur: Kajian Tentang Ritual Muharram di Malang - Zahra, Butsainah; Ghozi, Ahmad; Fauziyah, Nailul (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study examines the Mbabar Mbubur tradition in Malang as a form of religious practice that integrates Islamic spirituality with Javanese local wisdom, within and beyond the framework of Clifford Geertz’s theory of cultural syncretism. Employing a qualitative approach based on library research, this study analyzes the transformation of calendrical slametan rituals which, in Geertz’s classic account (1960), were considered marginal and sporadic into a more structured and socially significant communal practice. The findings reveal that Mbabar Mbubur represents an adaptive and inclusive expression of Islam, manifested through ritual symbolism, communal food distribution, ancestral pilgrimage, and the reinforcement of social solidarity. This study argues that the tradition reflects a dynamic integration of religious variants (santri, abangan, and priyayi) that, in the contemporary context, transcends and reconfigures Geertz’s earlier typology. Theoretically, this research contributes to Islamic anthropology by repositioning local ritual as an active site of religious meaning-making, while empirically addressing the limited scholarly attention to specific ritual practices in Malang.